Art's asymptotic leadership: Arts leadership, education and the loss of autonomy. Issue 3 (1st September 2014) - Baldacchino, John
This article will mostly engage with arts leadership through a discussion that focuses on the arts, leadership and education, and how their convergence might have a direct impact on autonomy. Taking a meta-theoretical approach, the main argument is that arts leadership is an asymptotic state of affairs. Rather than pose art and leadership as antithetical events that necessitate forms of syntheses through identifiable contexts, the context for arts leadership represents a contiguous space where art and leadership continuously seek a mutual way of preserving their integrity in an asymptotic relationship. If this relationship turns into a synthesis, both art's autonomy and the ability to lead creatively are neutralized. The aim is to question the various implications that bring together the autonomous spheres of the arts, education and leadership, while inviting the reader to draw his or her own conclusions critically and autonomously. To clarify this approach, this article straddles across several horizons, including: arts practice as a sphere of autonomous dispositions and the political implications that follow; education as a horizon that educes – leads out – through the pedagogical exits that are offered by the arts; and art's anti-systemic pedagogy, where art's autonomy becomes a possibility of unlearning systems.